An introduction to librarianship - Corbett, Edmund V. (London : Clarke, 1966)
The book dealt with the introductory aspect of librarianship and would be useful for those taking examination on the subject matter.
Includes bibliographical references and index.
kjo 16/01/2019
Loans
Keywords: Library science